ANALYSIS OF THE IMPACT OF DIGITAL TECHNOLOGIES ON THE DEVELOPMENT OF ENTREPRENEURIAL ENTITIES - RUDACHENKO, Olha; KONENKO, Vitalina; TARARUIEV, Iurii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
It has been proven that in the modern world, where global digital transformation is radically altering the business environment, researching the impact of digital technologies on the development of entrepreneurial entities and the economy of Ukraine as a whole is extremely relevant. Digital technologies offer new opportunities to enhance the efficiency of management processes, optimize production, reduce costs, and improve entrepreneurial entities competitiveness. At the same time, they create new challenges such as the need to adapt business models, manage data, and ensure cybersecurity.The article provides a comprehensive analysis of the impact of digital technologies on business processes, including the automation of management and production processes, the implementation of electronic management systems, and the use of digital communication channels. The research shows how these technologies help reduce risks associated with human factors, increase the speed of response to changes in demand, and minimize errors in order fulfillment. It has been demonstrated that, in the context of growing competition and changing consumer preferences, active use of social media, e-commerce, and other digital channels is crucial for attracting customers and maintaining communication with them. However, the implementation of digital technologies requires careful planning to minimize potential negative outcomes.Analysis of data on the use of information and communication technologies during the war period has shown a significant decline and reduction in the number of entrepreneurial entities engaged in e-commerce. At the same time, digital technologies provide new opportunities for business development by creating a multi-channel experience for consumers and contributing to the modernization of business processes. Future prospects include in-depth exploration of innovative solutions such as artificial intelligence and the Internet of Things, which could significantly enhance economic efficiency and competitive advantages for entrepreneurial entities.
Keywords: entrepreneurial entities; entrepreneurship; digital technology; development strategy; factors of influence